Mass spectrometry in the pharmacokinetic studies of anticancer natural products. Issue 2 (17th August 2015) - Crotti, Sara; Posocco, Bianca; Marangon, Elena; Nitti, Donato; Toffoli, Giuseppe; Agostini, Marco
Abstract : In the history of medicine, nature has represented the main source of medical products. Indeed, the therapeutic use of plants certainly goes back to the Sumerian and Hippocrates and nowadays nature still represents the major source for new drugs discovery. Moreover, in the cancer treatment, drugs are either natural compounds or have been developed from naturally occurring parent compounds firstly isolated from plants and microbes from terrestrial and marine environment. A critical element of an anticancer drug is represented by its severe toxicities and, after administration, the drug concentrations have to remain in an appropriate range to be effective. Anyway, the drug dosage defined during the clinical studies could be inappropriate for an individual patient due to differences in drug absorption, metabolism and excretion. For this reason, personalized medicine, based on therapeutic drug monitoring (TDM), represents one of most important challenges in cancer therapy. Mass spectrometry sensitivity, specificity and fastness lead to elect this technique as the Golden Standard for pharmacokinetics and drug metabolism studies therefore for TDM. This review focuses on the mass spectrometry‐based methods developed for pharmacokinetic quantification in human plasma of anticancer drugs derived from natural sources and already used in clinical practice. Particular emphasis was placed both on the pre‐analytical and analytical steps, such as: sample preparation procedures, sample size required by the analysis and the limit of quantification of drugs and metabolites to give some insights on the clinical practice applicability. © 2015 Wiley Periodicals, Inc. Mass Spec Rev. 36:213–251, 2017